BUSINESS PLAN ANALYSIS OF GOAT FARMING IN AL-AMIN LIVING LAB AND INDUSTRIAL PARK - Lubis, Hidayati Purnama; Siswoyo, Purwo; Rangkuty, Dewi Mahrani; Dewi, Tridia Kumala (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
The purpose of this research is to study and analyze the business plan for goat farming in the Al-Amin Living Lab and Industrial Park area in Kutalimbaru District, Sampe Cita Village. This type of research is descriptive qualitative research with a literature study research method through literature studies sourced from journals of previous research results. The results of this research explain that the business plan needs to be developed to educate the local community on how to start a new goat farming business to improve the standard and quality of life of the community in terms of the economy. In addition, the business plan aims to create a sustainable competitive advantage by maximizing market profits to achieve above-average business profits.